Pseudogenes in Cardiovascular Disease - Qi, Yanyan; Wang, Xi; Li, Wenbo; Chen, Dongchang; Meng, Hua; An, Songtao (Frontiers in Molecular Biosciences, 2021)
Cardiovascular disease is the main disease that affects human life span. In recent years, it has been increasingly addressed at the molecular levels and pseudogenes are revealed to be involved the pathogenesis and development of cardiovascular diseases. Pseudogenes are non-coding homologs of protein-coding genes and were once called "junk gene". Since they are highly homologous to their functional parental genes, it is somewhat difficult to distinguish them. With the development of sequencing technology and bioinformatics, pseudogenes have become readily identifiable. Recent studies indicate that pseudogenes are closely related to cardiovascular diseases. This review provides an overview of pseudogenes and their roles in the pathogenesis of cardiovascular diseases and would further our understanding of cardiovascular disease at the molecular level and help develop new biomarkers and therapeutic approaches to prevent and treat the disease.